Recognition and Removal of Amyloid‐β by a Heteromultivalent Macrocyclic Coassembly: A Potential Strategy for the Treatment of Alzheimer's Disease - Wang, Hui; Xu, XinXin; Pan, Yu‐Chen; Yan, YuXing; Hu, Xin‐Yue; Chen, RunWen; Ravoo, Bart Jan; Guo, Dong‐Sheng; Zhang, Tao (Advanced materials (Weinheim), 2021)
The imbalance of amyloid‐β (Aβ) production and clearance causes aggregation of Aβ1‐42 monomers to form fibrils and amyloid plaques, which is an indispensable process in the pathogenesis of Alzheimer's disease (AD), and eventually leads to pathological changes and cognitive impairment. Consequently, Aβ1‐42 is the most important target for the treatment of AD. However, developing a single treatment method that can recognize Aβ1‐42, inhibit Aβ1‐42 fibrillation, eliminate amyloid plaques, improve cognitive impairments, and alleviate AD‐like pathology is challenging. Here, a coassembly composed of cyclodextrin (CD) and calixarene (CA) is designed, and it is used as an anti‐Aβ therapy agent. The CD–CA coassembly is based on the previously reported heteromultivalent recognition strategy and is able to successfully eliminate amyloid plaques and degrade Aβ1‐42 monomers in 5xFAD mice. More importantly, the coassembly improves recognition and spatial cognition deficits, and synaptic plasticity impairment in the 5xFAD mice. In addition, the coassembly ameliorates AD‐like pathology including prevention of neuronal apoptosis and oxidant stress, and alteration of M1/M2 microglial polarization states. This supramolecular approach makes full use of both molecular recognition and self‐assembly of macrocyclic amphiphiles, and is a promising novel strategy for AD treatment. A heteromultivalent coassembly composed of cyclodextrin and calixarene (CD–CA coassembly) according to the composition of amino acids in Aβ1‐42 effectively recognizes and disaggregates Aβ1‐42 fibrils. Intranasal administration of the CD–CA coassembly eliminates amyloid plaque and neurodegeneration in the brain, and improves cognitive deficits in 5xFAD mice. This supramolecular approach is a promising novel strategy for treatment of Alzheimer's disease (AD).